Meizhou Dongpo Restaurant Group - McFarlan, F. Warren (Franklin Warren); Wu, Weiku; Guo, Jia ([London] : SAGE, 2016)
At the end of 2013, leaving the opening festivities for the 93rd Meizhou Dongpo branch restaurant in Shunyi, Beijing, Wang Gang was in a good mood. He felt a bit weary as he was driven back home, gazing at the night out of the car window. Looking back at Meizhou Dongpo's development over the past seventeen years, Wang Gang reflected on various aspects of his life.
Originally Published in: McFarlan, F. W., Wu, W., & Guo, J. (2014). Meizhou Dongpo Restaurant Group. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Meizhou Dongpo Restaurant Group; Restaurants -- Case studies